Money in monetary policy design: Monetary cross-checking in the New-Keynesian Model - Guenter W. Beck; Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
In the New-Keynesian model, optimal interest rate policy under uncertainty is formulated without reference to monetary aggregates as long as certain standard assumptions on the distributions of unobservables are satisfied. The model has been criticized for failing to explain common trends in money growth and inflation, and that therefore money should be used as a cross-check in policy formulation (see Lucas (2007)). We show that the New-Keynesian model can explain such trends if one allows for the possibility of persistent central bank misperceptions. Such misperceptions motivate the search for policies that include additional robustness checks. In earlier work, we proposed an interest rate rule that is near-optimal in normal times but includes a cross-check with monetary information. In case of unusual monetary trends, interest rates are adjusted. In this paper, we show in detail how to derive the appropriate magnitude of the interest rate adjustment following a significant cross-check with monetary information, when the New-Keynesian model is the central bank's preferred model. The cross-check is shown to be effective in offsetting persistent deviations of inflation due to central bank misperceptions.
urn:nbn:de:hebis:30-71820
Keywords: E32; E41; E43; E52; E58; 330; Monetary Policy; New-Keynesian Model; Money; Quantity Theory; European Central Bank; Policy Under Uncertainty; Geldpolitik; Zentralbank; Entscheidung bei Unsicherheit; Zins; Ungleichgewichtstheorie